Cognitive Training Effectiveness on Memory, Executive Functioning, and Processing Speed in Individuals With Substance Use Disorders: A Systematic Review - Caetano, Tânia; Pinho, Maria Salomé; Ramadas, Eduardo; Clara, Cátia; Areosa, Timóteo; Dixe, Maria dos Anjos (Frontiers in Psychology, 2021)
Background: Cerebral neuroplasticity is compromised due to substance abuse. There is damage to neuronal areas that are involved in memory and executive functioning. Treatments with worse outcomes are often associated with cognitive deficits that have resulted from substance dependence. However, there is evidence that cognitive training can lead to improvements in cognitive functions and can be useful when treating addictions. This systematic review aims to synthesize evidence on the effectiveness of cognitive training in memory, executive functioning, and processing speed in individuals with substance use disorder (SUD). Methods: The Joanna Briggs Institute’s PICO strategy was used to develop this systematic literature review. Four databases were searched (PubMed, the Cochrane Library, Web of Science, and PsycINFO) to identify controlled randomized clinical studies and quasi-experimental studies, in English, Portuguese, and Spanish, from 1985 to 2019. The literature found was examined by two independent reviewers, who assessed the quality of studies that met the inclusion criteria. The Cochrane risk-of-bias tool for the randomized controlled trials and the ROBINS-I tool for non-randomized studies were used to assess the risk of bias. In data extraction, the Cochrane Handbook for Systematic Reviews was considered. Results: From a total of 470 studies, 319 were selected for analysis after the elimination of duplicates. According to the inclusion criteria defined, 26 studies were eligible and evaluated. An evaluation was performed considering the participant characteristics, countries, substance type, study and intervention details, and key findings. Of the 26 selected studies, 14 considered only alcoholics, six included participants with various SUD (alcohol and other substances), three exclusively looked into methamphetamine-consuming users and another three into opioid/methadone users. Moreover, 18 studies found some kind of cognitive improvement, with two of these reporting only marginally significant effects. One study found improvements only in measures similar to the training tasks, and two others had ambiguous results. Conclusions: The included studies revealed the benefits of cognitive training with regard to improving cognitive functions in individuals with SUD. Memory was the most scrutinized cognitive function in this type of intervention, and it is also one of the areas most affected by substance use.